Prescription patterns of outpatients and the potential of multiplexed pharmacogenomic testing. Issue 3 (3rd July 2020) - Chan, Sze Ling; Liew, Hariz Zhen Wei; Nguyen, Francis; Thumboo, Julian; Chow, Wan Cheng; Sung, Cynthia
Abstract : Background: Pre‐emptive pharmacogenomic (PGx) testing is potentially an efficient approach to improve drug safety and efficacy but the target population to test is unclear. Objectives: We aim to describe the prescription pattern of PGx drugs among adult medical outpatients. Methods: We estimated the 5‐year cumulative incidence (CI) for receiving three groups of PGx drugs using competing risks analysis: (i) all PGx drugs, (ii) PGx drugs with guidelines and (iii) PGx drugs with serious clinical effects. Comparisons of CIs were also done by patient characteristics using Gray's test. Results: The 5‐year CIs of receiving any new PGx drug, PGx drug with guidelines and serious clinical effects were 42.6%, 37.3% and 13.7%, respectively. The 5‐year CI of receiving any new PGx drug was higher for patients >40 years old (43.6% vs ≤40 years old 36.0%, P < 2.2 × 10 −22 ), Malays and Indians (50.3% and 49.8% vs Chinese 31.1%, P < 2.2 × 10 −22 ), those who attended one of the following four specialties at the index visit compared to other specialties (infectious diseases [46.2% vs 42.6%, P = 2.9 × 10 −4 ], psychiatry [48.3% vs 42.3%, P = 7.4 × 10 −13 ], renal [49.8% vs 40.9%, P < 2.2 × 10 −22 ], and rheumatology and immunology [54.8% vs 41.7%, P < 2.2 × 10 −22 ]) and those prescribed ≥5 drugs at index visit (51.7% vs 0‐4 drugs 41.7%, P < 2.2 × 10 −22 ). Conclusions: Medical outpatients have a substantial probability of benefiting from pre‐emptive PGx testing and this is higher in certain subgroups of patients.